Fractionation of Garcinia Mangostana Fruit Pericarp Cellulase Assisted Extracts by Preparative Thin Layer Chromatography and High Performance Liquid Chromatography - Nugroho, Titania Tjandrawati; Puja, Krisna; Eryanti, Yum; Miranti, Miranti (Jurnal Natur Indonesia, 2020)
The polar extract of Mangosteen (Garcinia mangostana) fruit pericarp obtained by cellulase assisted ethanol extraction has strong antioxidant activity, giving an average 2,2 diphenyl-1 pykrylhydrazyl (DPPH) radical  scavenging IC50 of 13.9 µg/mL. In order to elucidate the chemical component from this extract that is responsible for the high antioxidant activity, fractionation of the extract should firstly be performed. In this paper we show results of preparative fractionation of the polar extract by two methods, namely preparative Thin Layer Chromatography (PTLC) and preparative High Performance Liquid Chromatography (PHPLC). PTLC used Silica Gel G60 plates, with a hexane:ethyl acetate (6:4) eluent. PHPLC was a reverse phase method, using C18 column and water:acetonitrile gradient elution. 4 fractions from PTLC and 6 fractions from PHPLC were collected and their antioxidant activity analyzed. Both methods gave separated fractions with lower antioxidant activity than the unfractionated original crude extracts, showing that the strong antioxidant activity of Mangosteen pericarp polar extracts maybe due to the concerted synergetic effect of several compounds, rather than a single isolated compound. It also shows the high degree of difficulty in separating mangosteen pericarp polar components having antioxidant activity for further structural analysis.